The changing face of the Mediterranean – Land cover, demography and environmental change: Introduction and overview. (May 2019) - Bevan, Andrew; Palmisano, Alessio; Woodbridge, Jessie; Fyfe, Ralph; Roberts, C Neil; Shennan, Stephen
This paper introduces a special issue on The Changing Face of the Mediterranean: Land Cover, Demography, and Environmental Change, which brings together up-to-date regional or thematic perspectives on major long-term trends in Mediterranean human–environment relations. Particularly, important insights are provided by palynology to reconstruct past vegetation and land cover, and archaeology to establish long-term demographic trends, but with further significant input from palaeoclimatology, palaeofire research and geomorphology. Here, we introduce the rationale behind this pan-Mediterranean research initiative, outline its major sources of evidence and method, and describe how individual submissions work to complement one another.